Effect of high inlet temperature of spray dryer on viability of microencapsulated Trichoderma asperellum conidia - Ishak, A A; A Zulkepli, F R; M Hayin, N F; Md Zin, Noor Hasniza; Sapak, Z (IOP Publishing, 2021)
In recent years, the use of spray drying for microencapsulating beneficial microbes has gained the interest of researchers, mainly due to dried powder formulation could prevent contamination and prolong self-life of the microbes. The major constraint of spray drying is conidia could lose viability during the drying process due to heat. In this present study, the effect of spray drying inlet temperature on viability of microencapsulated Trichoderma asperellum conidia was assessed. A blend biopolymer of gum Arabic and maltodextrin in ratio of 1:1 was used to microencapsulate the conidia at 150, 160 and 170oC inlet temperatures of spray drying process. Assessment of conidia viability was performed based on conidia percent survival of spray dried (PSsd) and survival increase (SI) unit values. Viability of the microencapsulated conidia was also evaluated their shelf life stored at two different temperatures which were at 28 ±2˚C and 4±2˚C for 40 weeks. The finding showed that viability of microencapsulated conidia was optimum obtained at inlet temperature of 170˚C with 68.2% of PSsd and SI and 17.7 units of SI compared to 15.9% and 1.5 unit respectively obtained for 160oC and 0.2% and 0.7 unit for 150oC. The highest inlet temperature has showed the highest viability compared to lower temperatures. Conidia stored at low temperature of 4 ±2˚C has survived longer up to 40 weeks that were confirmed via the viability test. High inlet temperature of 170oC was desirable to enhance survivability and viability of the conidia to be used as biocontrol agent up to 40 weeks at low temperature storage. These microencapsulated conidia could be further tested on their capability to inhibit the pathogen of pineapple disease